Women and poverty dynamics : the case of Germany and Britain - Ruspini, Elisabetta (Journal of European social policy, 1998)
Abstract (s. 291).
Keywords: köyhyys : naiset : Iso-Britannia; köyhyys : naiset : Saksan liittotasavalta